Study of a residential boiler under start-transient conditions using a tire pyrolysis liquid (TPL)/diesel fuel blend. (15th October 2015) - García-Contreras, Reyes; Martínez, Juan Daniel; Armas, Octavio; Murillo, Ramón; García, Tomás
Highlights: Potential for using high concentration of TPL fuel in boilers. A slight increase of efficiency from 50/50 TPL fuel blended with diesel fuel was observed. 50/50 TPL blend produced similar CO and THC emissions to diesel fuel but higher particle number concentration. Trade off NOx-PM 50/50 TPL fuel was obtained. Abstract: Tire pyrolysis liquid (TPL)/diesel fuel blend (50/50 vol.%) was fed in a residential boiler unit of 29.1 kW of nominal power, assessing its potential use as alternative heating fuel oil (HFO) for domestic heating. Process performance was compared to that observed for conventional diesel fuel. Both, 50/50 blend and reference diesel fuel were tested at three different positions of the screw which regulates the fuel–air ratio (optimized for diesel fuel). Different operating parameters, such as water and exhaust temperature profiles and boiler efficiency, were evaluated. In addition, concentrations of pollutant gases (CO, NOx and THC) and particulate matter (PM) through total number of particles were measured. The study was carried out under the most critical transient process for any thermal machine: the start-up. Regarding to the fuel effect, the 50/50 blend gives thermal efficiencies slightly higher compared to those found for diesel fuel at all positions tested. In addition, both CO and THC concentrations were slightly lower for the alternative fuel compared to those found for the conventional fuel, being more representative at the lower relative fuel ratio (position 5). However, PM concentrations for 50/50 blend were higher to those found for diesel fuel at all positions of the regulator screw. This work demonstrates the great potential for using a high proportion of TPL fuel blended with diesel fuel without the need of modifying original regulation parameters of boiler, although some properties of TPL should be improved in order to decrease the PM concentrations.